2015
DOI: 10.17957/ijab/17.3.14.170
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins Production by Fusarium and Aspergillus Species Isolated from Cornmeal

Abstract: Corn is a vital food source for human consumption, animal feed as well as industrial processing. However, corn faces repeated spoilage and contamination by a huge range of fungi especially by Fusarium and Aspergillus species. These fungi are known of producing mycotoxins such as fumonisins (FBs), moniliformin (MON), zearalenone (ZEA), beauvericin (BEA) and aflatoxins (AFs). The main objective of this study was to quantify the mycotoxins produced by both fungi associated with cornmeal in Malaysia. The extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Later, two separate studies that were conducted for mycotoxin contamination in cornmeal had described the incidence of aflatoxins in most samples and found (in decreasing order) fumonisins (i.e., FB 1 and FB 2 ), OTA, DON, HT-2, T-2, and ZEN [78,79]. Further, another study on cornmeal [80] found that all F. verticillioides isolates investigated (n = 16/16) were able to produce FB 1 , and a high number of A. flavus isolates were able to produce AFB 1 (n = 29/40). Moreover, they also reported that F. proliferatum, F. semitectum, and F. verticillioides were able to produce moniliformin (MON, n = 3/3, n = 6/6, and n = 6/7, respectively) and beauvericin (BEA, n = 3/3, n = 4/6, and n = 5/7, respectively) in the samples.…”
Section: Mycotoxigenic Potential Of Mycotoxigenic Isolates From Two Pmentioning
confidence: 99%
“…Later, two separate studies that were conducted for mycotoxin contamination in cornmeal had described the incidence of aflatoxins in most samples and found (in decreasing order) fumonisins (i.e., FB 1 and FB 2 ), OTA, DON, HT-2, T-2, and ZEN [78,79]. Further, another study on cornmeal [80] found that all F. verticillioides isolates investigated (n = 16/16) were able to produce FB 1 , and a high number of A. flavus isolates were able to produce AFB 1 (n = 29/40). Moreover, they also reported that F. proliferatum, F. semitectum, and F. verticillioides were able to produce moniliformin (MON, n = 3/3, n = 6/6, and n = 6/7, respectively) and beauvericin (BEA, n = 3/3, n = 4/6, and n = 5/7, respectively) in the samples.…”
Section: Mycotoxigenic Potential Of Mycotoxigenic Isolates From Two Pmentioning
confidence: 99%
“…Nirmaladevi et al (2016) reported that other species such as F. oxysporum were responsible for more than 80% of post-harvest rots in tomato fruits in India. Fusarium species involved in this rot contaminate tomato fruits with various mycotoxins (Wisniewka et al, 2011;Maja et al, 2012;Zainudin et al, 2015;Wamalwa et al, 2018;Srinivas et al, 2019). These secondary metabolites produced by fungi are known to be toxic to many organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Beauvericin ( Figure 1 ), a cyclic hexadepsipeptide with alternating N -methyl-phenylalanyl and D -hydroxy-isovaleryl residues, was firstly discovered from the entomopathogenic fungus Beauveria bassiana [ 3 ]. As one of chemical contaminants, it is mainly detected in maize kernels and derived products infected by phytopathogenic fungi, including Aspergillus [ 4 ], Cordyceps [ 5 ], and Fusarium [ 6 9 ] species. Originally, this cyclodepsipeptide was found to be toxic to human and animal tissues and cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%